Slowly eroding lesions in multiple sclerosis. (March 2017) - Sethi, Varun; Nair, Govind; Absinta, Martina; Sati, Pascal; Venkataraman, Arun; Ohayon, Joan; Wu, Tianxia; Yang, Kelly; Shea, Colin; Dewey, Blake E; Cortese, Irene CM; Reich, Daniel S
Background: At autopsy, 20%–40% of chronic multiple sclerosis (MS) lesions are labeled "slowly expanding" and feature myelin phagocytosis at the lesion edge. As pathological lesion classification relies on a single, terminal time point, the rate of lesion expansion cannot be directly measured. Objective: To study long-term volume changes in individual MS lesions. Methods: Volumes of individual lesions on proton density magnetic resonance imaging (MRI) acquired between 1992 and 2015 were measured in 22 individuals (one lesion per person). After correction for acquisition protocol, a mixed model evaluated lesion volume changes. Results: The mean (standard deviation) lesion volume at baseline was 142 (82) mL, falling to 74 (51) mL after 16 (3) years. All lesions shrank over time. Change in lesion volume did not correlate with change in supratentorial brain volume ( p = 0.33). In simulations, the results could be explained by a process of slow radial expansion superimposed on substantially more rapid resorption of damaged tissue. Conclusion: We noted sustained radiological contraction of MS lesions, a surprising result given that fresh myelin breakdown products within chronic active lesions are observed relatively frequently at autopsy. Therefore, the primary pathological process in chronic lesions, even those described as "slowly expanding, " is likely to be tissue loss.